Macroprudential Regulation, Quantitative Easing, and Bank Lending - Orame, Andrea; Ramcharan, Rodney; Robatto, Roberto (Review of Financial Studies, 2025)
Abstract We show that widely used macroprudential regulations that rely on historical cost accounting (HCA) to insulate banks’ balance sheets from financial market volatility significantly affect the transmission of monetary policy onto bank lending. Using detailed supervisory data from Italian banks, we find that HCA mutes the transmission of quantitative easing and other monetary policies that affect the long end of the yield curve, weakening the effectiveness of interventions aimed at reducing firm credit constraints. We suggest alternative policies that have the benefits of HCA but allow monetary policy to pass through.